Communal Constructivism and Networked Learning: Reflections on a Case Study - Pountney, Richard; Parr, Sadie; Whittaker, Vic (Proceedings of the International Conference on Networked Learning, 2002)
Holmes et al. (2001) have suggested that the advent of new educational technologies warrants a new kind of educational theory - ’communal constructivism.’ Communal constructivism attempts to move beyond social constructivism and capture specific elements of the additional value that C&IT applications bring to the learning and teaching environment. Our paper will critically evaluate the usefulness of Holmes et al’s ideas through a case study of the way in which a virtual learning environment, Blackboard, is currently being used to support students on a level three unit ICT in an Educational Context at Sheffield Hallam University.